Composition, Distribution and Constraining Factors of Fe Isotope (δ56Fe) in the Surface Soils of the Tibetan Plateau - Ting Wei; Zhiwen Dong; Eric Parteli; Xiaoli Liu; Shichang Kang; Yaping Shao (Journal of Earth Science, 2026)

An integrated modeling framework for groundwater contamination risk assessment in arid, data-scarce environments - Elham Rafiei-Sardooi; Ali Azareh; Hossein Ghazanfarpour; Eric Josef Ribeiro Parteli; Mohammad Faryabi; Saeed Barkhori (Acta Geophysica, 2024)

Evaluation of precipitation reanalysis products for regional hydrological modelling in the Yellow River Basin - Cong Jiang; Eric J. R. Parteli; Qian Xia; Yaping Shao (Theoretical and Applied Climatology, 2024)
This study evaluates six precipitation reanalysis products for the Yellow River Basin using gridded rain gauge data, runoff data and the Atmospheric and Hydrological Modelling System (AHMS) simulations. The assessment begins with comparing the annual, seasonal, monthly and daily precipitation of the products with gridded rain gauge data. The AHMS is then run with each of the precipitation reanalysis products under two scenarios: one with calibrated rainfall-runoff and the other without. The simulated streamflow is then compared with the corresponding observations. It is found that non-gauge-corrected products tend to overestimate precipitation, especially for mountainous regions. Amongst the six products evaluated, the China Meteorological Forcing Dataset (CMFD) and WATCH Forcing Data methodology applied to ERA5 (WFDE5/CRU+GPCC) are identified as the most accurate products, supported by both statistical and hydrological comparisons. This consistency in statistical and hydrological comparisons suggests the potential applicability of the hydrological comparison method using the AHMS in ungagged catchments, even in the presence of significant anthropogenic impacts. Furthermore, the calibration of the hydrological model significantly impacts the model’s response to precipitation, effectively compensating for deficiencies in rainfall data within certain limits. This study highlights accurate representation of extreme rainfall events in precipitation products has a significant impact on calibrated soil parameters and is particularly important in hydrological modelling. It enhances our understanding of the reliability of hydrological simulations and provides valuable insights for the assessment of precipitation reanalysis products in large arid and semiarid basins affected by human activities.